Interweaving of the sources and forms of a firm's competitive advantage: A critical review of the adequacy of existing schools of thought - Tomaz Cater (Journal for East European Management Studies, 2005)
The paper examines how the sources and forms of competitive advantage interweave and what does this mean for the existing theory on competitive advantage. We found out that all sources of competitive advantage should be classified into external and internal category. Consequently, we believe it is reasonable to discuss only two schools, i.e. the internal school based on resources, capabilities and knowledge and the external school based on the industrial organisation. The relation between them should not be understood as being solely competitive but also complementary, which means that the mystery of creating a competitive advantage cannot be explained by any school alone. – – Der Aufsatz untersucht, inwiefern die Ursprünge und Formen von Wettbewerbsvorteilen miteinander verflochten sind und wie sich dies auf die Theorie des Wettbewerbsvorteiles auswirkt. Die Ursprünge des Wettbewerbsvorteiles lassen sich in externe und interne Gruppen einteilen. Als Konsequenz daraus ist es sinnvoll, lediglich zwei Ansichten zu diskutieren, die interne Lehre, die auf Ressourcen, Fähigkeiten und Wissen zurückgreift und die externe, die auf der industriellen Organisation basiert. Die Beziehung der zwei Lehren sollte nicht als konkurriend sondern als ergänzend aufgefasst werden, was bedeutet, dass das Rätsel der Schaffung eines Wettbewerbsvorteiles nicht alleine von einer Lehre erklärt werden kann.
Keywords: 650; Firm; competitive advantage; industrial organisation; resources; capabilities; knowledge